Fluent temporal logic for discrete-time event-based models. - Letier, Emmanuel (Software engineering notes.)
Fluent model checking is an automated technique for verifying that an event-based operational model satisfies some state-based declarative properties. The link between the event-based and state-based formalisms is defined through "fluents" which are state predicates whose value are determined by the occurrences of initiating and terminating events that make the fluents values become true or false, respectively.The existing fluent temporal logic is convenient for reasoning about untimed event-based models but difficult to use for timed models. The paper extends fluent temporal logic with temporal operators for modelling timed properties of discrete-time event-based models. It presents two approaches that differ on whether the properties model the system state after the occurrence of each event or at a fixed time rate. Model checking of timed properties is made possible by translating them into the existing untimed framework.